Exergetic comparison of three different processing routes for yellow pea (Pisum sativum): Functionality as a driver in sustainable process design. (10th May 2018) - Geerts, Marlies; van Veghel, Amber; Zisopoulos, Filippos K.; van der Padt, Albert; Jan van der Goot, Atze
Abstract: Today, the environmental performance of food products and food ingredients is mostly evaluated on the basis of mass (MJ/kg). However, food ingredients are generally added to obtain a specific functionality, such as increased viscosity or modification of the texture. The functionality obtained is not always fully correlated with the amount of ingredients added. This can be especially true when ingredients are produced using different processes. We have investigated how the functionality of ingredients can be included in a sustainability analysis. Here, we have combined exergy analysis and functionality to select the most beneficial process route for fractionation of yellow pea flour. We assess the resource use efficiency of three fractionation processes for yellow pea flour: conventional wet fractionation (CWF), dry fractionation (DF), and a mild wet fractionation (MWF). Exergy analysis based on mass showed that DF has the highest exergy efficiency (99%), due to the (almost) complete use of raw materials, followed by the MWF (54%) and CWF (35%). Interestingly, even though DF is identified as the preferred technology on exergy analysis based on mass, DF is not the preferred option when the results are expressed as MJ/functionality. In that case, more DF starch is needed to obtain the desired functionality, resulting in higher exergy consumption for DF. This study shows that mass-based exergy analysis could result in an exergy efficient process route, whereas for functional application in a food product, this process route is not always the most efficient with regard to resource. This outcome demonstrates the need for inclusion of functionality in sustainability analysis. Highlights: Exergy analysis on mass base does not always lead towards most sustainable solution. The inclusion of functionality in exergy analysis influences the interpretation. Fractionation methods should aim for optimal efficiency in terms of functionality. Waste minimisation should consider the material gain as well as the immaterial input.